Label-free, fast, 2-photon volume imaging of the organization of neurons and glia in the enteric nervous system - Hazart, Doriane; Delhomme, Brigitte; Oheim, Martin; Ricard, Clément (Frontiers in Neuroanatomy, 2023)
The enteric nervous system (ENS), sometimes considered as a ‘second brain’ due to its large autonomy from central circuits, is made up of interconnected plexuses organized in a mesh-like network lining the gastrointestinal tract. Originally described as a leading actor of the regulation of digestion, bowel advance and intestinal secretion, its implication in various neuropathologies has recently been demonstrated. However, with only a few exceptions, its morphology and pathologic alterations have been studied on thin sections of the intestinal wall or in dissected explants. Due to its intricate morphology, precious information on its three-dimensional (3-D) architecture and connectivity is often lost. In this context, we have developed a fast, label-free 3-D imaging method of the ENS, based on intrinsic signals of the tissue. We used a custom, fast tissue-clearing protocol based on a high refractive-index aqueous solution, and then characterized the autofluorescence signals arising from the various cellular and sub-cellular components of the ENS. Validation by immunofluorescence and spectral recordings complete our label-free characterization. Finally, we demonstrate the fast acquisition of detailed 3-D image stacks from unlabeled mouse intestine, across the whole intestinal wall and including both the myenteric and submucosal enteric nervous plexuses using a new spinning-disk two-photon microscope. The combination of fast clearing (less than 15 min for 73 % transparency), autofluorescence detection and rapid volumetric imaging (less than a minute for the acquisition of s z-stack of 100 planes (150*150 µm) at 300-nm spatial resolution) paves the way for new applications in fundamental and clinical research.